Mixed-race ancestry and its impact on the facial reconstruction process - Robinson, Jermaine Carl (2010)
Various facial reconstruction techniques are used by forensic artists to assist in the identification of human remains. In establishing the biological profile for completion of a facial reconstruction, often the most difficult yet most important determination to make is that of race and/or ancestry of the decedent. By purposefully creating a facial reconstruction of an unidentified presumed mixed-race female decedent, staying true to the tissue depth information arrived at as a result of this researcher’s tests to determine her race, this author plans to investigate if any biases arise among any potential parties involved in the forensic identification process. This investigation was conducted through polling students at a predominantly white university and a predominantly black university in order to compare how individuals of different races and ancestral backgrounds view race and ancestry and to compare their responses. A public survey regarding the completed clay facial reconstruction was conducted at Louisiana State University (LSU) and Southern University (SU), both located in Baton Rouge, Louisiana. Participants answered questions regarding the race and ancestry of the woman represented by the clay facial reconstruction (134 total; LSU = 71, and SU = 63). The responses from the surveys between both campuses were similar. The largest number of students believed the woman’s race to be white (41.8%) and her ancestry to be European (28.4%) when compared to the other labels. This researcher employed the Pearson’s chi-square test to assess if the responses to the survey were significantly different (5% significance level with three significant digits for rounding). The comparisons of survey responses found a significant difference between the two universities for the race identification only; all other comparisons based on sex, self-identified race of the respondent, and responses to ancestry were not significantly different. Additionally, the most frequently referenced facial features were the nose and the lips, respectively, in the surveys. Although the responses of the students of the two institutions did not deviate significantly in the way in which they identified specific racial features, their answers were diverse. Future research on this topic should be motivated by questioning if scientific practices are sufficient enough to capture this issue — an issue which is also socially scientifi